Hubungan Tingkat Pendidikan dengan Kepatuhan Minum Obat Pasien Hipertensi - Maria Agustina Ermi Tri Sulistiyowati; Yohanes Tri Anugrahanto; Maria Suryani (Jurnal Kesehatan Elisabeth, 2025)
Non-adherence to medication is an important problem in the management of hypertension. Thos problem was founded in patient with various education level. However, the study about relationship between level of education and medication adherence is still inconclusive. This study aims to determine the relationship between level of education and medication adherence in hypertensive patients.The research design used was cross sectional. Ninety hypertensive patients at Mijen community health center was taken using convenience sampling technique. Data were obtained using the respondent's character questionnaire and the ProMAS (Probabilistic Medication Adherence Scale) questionnaire.The majority of respondents' education level is elementary school, as many as 26 respondents (28.9%). The majority of respondents' medication adherence level was moderate-high, as many as 45 respondents (50%). Spearman test results obtained r=0.236 and p-value= 0.025.There is a significant positive relationship between the level of education and the level of compliance with taking medication in hypertensive patients.